Megahertz emission of massive early-type stars in the Cygnus region. (2020) - Benaglia, P.; De Becker, M.; Ishwara-Chandra, C. H.; Intema, H. T.; Isequilla, N. L.
Abstract: Massive, early-type stars have been detected as radio sources for many decades. Their thermal winds radiate free–free continuum and in binary systems hosting a colliding-wind region, non-thermal emission has also been detected. To date, the most abundant data have been collected from frequencies higher than 1 GHz. We present here the results obtained from observations at 325 and 610 MHz, carried out with the Giant Metrewave Radio Telescope, of all known Wolf-Rayet and O-type stars encompassed in area of 15 sq degrees centred on the Cygnus region. We report on the detection of 11 massive stars, including both Wolf-Rayet and O-type systems. The measured flux densities at decimeter wavelengths allowed us to study the radio spectrum of the binary systems and to propose a consistent interpretation in terms of physical processes affecting the wide-band radio emission from these objects. WR 140 was detected at 610 MHz, but not at 325 MHz, very likely because of the strong impact of free–free absorption (FFA). We also report—for the first time—on the detection of a colliding-wind binary system down to 150 MHz, pertaining to the system of WR 146, making use of complementary information extracted from the Tata Institute of Fundamental Research GMRT Sky Survey. Its spectral energy distribution clearly shows the turnover at a frequency of about 600 MHz, that we interpret to be due to FFA. Finally, we report on the identification of two additional particle-accelerating colliding-wind binaries, namely Cyg OB2 12 and ALS 15108 AB.